Co-As-Sn single crystal alloy, preparation method and application

By preparing Co-As-Sn single crystal alloy, the problem of narrow temperature range of existing linear magnetoresistive materials is solved, a wider operating temperature range and higher magnetic sensitivity are achieved, and the use needs of magnetic sensors under different temperature environments is met.

CN119900090AActive Publication Date: 2025-04-29SHAANXI NORMAL UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510101325.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-22
Publication Date
2025-04-29
Estimated Expiration
2045-01-22

AI Technical Summary

Technical Problem

The temperature range of existing linear magnetoresistive materials is relatively narrow and cannot meet the needs of magnetic sensors in different temperature environments.

Method used

Co-As-Sn single crystal alloy was prepared by mixing Co powder, As powder and Sn particles in a specific molar ratio, heating and cooling and crystallization were carried out to prepare a Co-As-Sn single crystal alloy with a wide temperature range.

Benefits of technology

The operating temperature range of Co-As-Sn single crystal alloy is achieved from 2K to 300K, maintaining high magnetic sensitivity and stability, and improving the anti-interference and accuracy of magnetic sensors.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119900090A_ABST
    Figure CN119900090A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of magnetic sensors, in particular to a Co-As-Sn single crystal alloy and a preparation method and application thereof.The Co-As-Sn single crystal alloy is prepared by conducting Sn element doping on Co and As, through Sn element doping, the energy band structure and the belite curvature of the alloy can be changed, then the magnetoresistance behavior of the alloy is influenced, and the magnetoresistance performance of the alloy is improved. The prepared Co-As-Sn single crystal alloy can still work normally as a linear magnetoresistance material at a low temperature, and the working temperature range is wider, so that the use requirement of a magnetic sensor is better met, and the magnetic sensor plays an important role in more fields. The problems that in the prior art, a linear magnetoresistance material is narrow in temperature range and cannot meet the use requirement of a magnetic sensor are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of magnetic sensors, and in particular to a Co-As-Sn single crystal alloy, a preparation method and application thereof. Background Art

[0002] The magnetoresistance effect is a physical phenomenon, specifically referring to the change in the resistance of certain metals or semiconductors with an applied magnetic field. The magnetoresistance effect is mainly caused by the deflection of carriers (such as electrons or holes) in a magnetic field due to the Lorentz force. This deflection increases the effective path length of the carriers in the conductor or semiconductor, which in turn causes a change in the resistance value. Specifically, when a magnetic field acts on a conductor or semiconductor, the carriers will be affected by the Lorentz force, causing their motion trajectory to deflect, thereby increasing the chance of carrier scattering in the material, resulting in increased resistance. It has been widely used and deeply studied in many fields such as materials science, electronics, and magnetism; among them, in materials science, the magnetoresistance effect can reflect the magnetic state of the material, such as ferromagnetism, antiferromagnetism, etc. By measuring the magnetoresistance effect, the magnetic parameters of the material such as the magnetization curve and coercive force can be understood. In addition, the lattice structure, defect distribution and other information of the material can also be indirectly understood, which can be used as one of the important indicators for evaluating material performance.

[0003] Since different magnetic materials have different magnetoresistance effects under the action of magnetic fields, this helps to distinguish and identify various magnetic materials. For example, the magnetoresistance of some metals or semiconductors generally increases quadratically with the magnetic field, saturates in the high field region, and its magnetoresistance changes linearly with the magnetic field, with a significant magnetoresistance effect. It is a linear resistance material. By testing the magnetoresistance of linear resistance materials, the size of the magnetic field applied by the outside world can be determined. Linear magnetoresistance materials have extremely wide application value and huge development potential in computer hard disk read heads, magnetic random access memory (MRAM), and magnetic sensors.

[0004] However, the temperature range of currently known linear magnetoresistance materials is relatively narrow, and magnetic sensors need to work in different temperature environments. If the temperature range of linear magnetoresistance materials is too narrow, the performance of the sensor may vary greatly under different temperature conditions, which will lead to inaccurate measurement results of the sensor or even malfunction, thus limiting the application of linear magnetoresistance materials in magnetic sensors. Therefore, finding a linear magnetoresistance material with strong magnetic response and a wide temperature range has become an urgent problem to be solved in the physics and electronic information science and technology communities. Summary of the invention

[0005] In view of the problem that the linear magnetoresistance material in the prior art has a narrow temperature range and cannot meet the use requirements of magnetic sensors, the present invention provides a Co-As-Sn single crystal alloy, a preparation method and an application.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions: The present invention provides a Co-As-Sn single crystal alloy, comprising Co, As and Sn, wherein the molar ratio of Co, As and Sn is (0.95-1.05): (0.75-0.85): (0.33-0.43).

[0007] Optionally include: Mixing Co powder, As powder and Sn particles to obtain a mixture; The mixture is heated and melted to obtain a prefabricated alloy melt; The prefabricated alloy melt is cooled and crystallized, and excess Sn is separated to obtain a Co-As-Sn single crystal alloy.

[0008] Optionally, the molar ratio of the Co powder, As powder and Sn particles is (0.95-1.05): (0.75-0.85): (9-11).

[0009] Optionally, the heating and melting temperature is 800° C. to 850° C., and the insulation time is 48 to 60 hours.

[0010] Optionally, the heating time for the heating and melting is 8 to 8.5 hours.

[0011] Optionally, the cooling rate of the cooling crystallization is 1 to 3°C / h.

[0012] Optionally, the method of cooling the prefabricated alloy melt to crystallize and separate excess Sn to obtain the Co-As-Sn single crystal alloy is: The prefabricated alloy melt is cooled to 500°C to 550°C at a cooling rate of 1 to 3°C / h, and excess Sn is separated to obtain a Co-As-Sn single crystal alloy melt; The Co-As-Sn single crystal alloy melt is cooled to room temperature in air to obtain a Co-As-Sn single crystal alloy.

[0013] Optionally, the heating to melt and the cooling to crystallize are both performed under vacuum conditions.

[0014] The present invention provides a Co-As-Sn single crystal alloy, which is prepared by the above method. The operating temperature range of the Co-As-Sn single crystal alloy is 2k to 300k.

[0015] Such as the application of Co-As-Sn single crystal alloy in magnetic sensors.

[0016] Compared with the prior art, the present invention has the following beneficial effects: The present invention discloses a Co-As-Sn single crystal alloy, comprising Co, As and Sn, wherein the molar ratio of Co, As and Sn is (0.95-1.05): (0.75-0.85): (0.33-0.43). Among them, Co is an important magnetic element, having good magnetic and electrical properties, and can improve the hardness and strength of the alloy in the Co-As-Sn single crystal alloy while maintaining good plasticity and toughness; As can improve the corrosion resistance and thermal stability of the Co-As-Sn single crystal alloy, so that the alloy can maintain its stable performance in harsh environments and extend its service life; Sn as a dopant in the magnetic material composed of Co and As can improve the band structure and Berry curvature of the Co-As-Sn single crystal alloy. The band structure is an important way to describe the energy state of electrons in solids, which determines the movement and distribution of electrons in solids. The Bailey curvature is a geometric property that describes the movement of electrons in solids. Its change can affect the orbital motion and spin motion of electrons, thereby affecting the magnetoresistance behavior of the alloy. By doping Sn, the band structure of the alloy changes, affecting the transport characteristics of electrons. This optimization enables the alloy to maintain a high magnetoresistance effect and stable performance at low temperatures, so that the Co-As-Sn single crystal alloy can still work normally at low temperatures as a linear magnetoresistance material, with a wider operating temperature range and stronger comprehensive performance, providing a new direction for the improvement and optimization of magnetic sensors. The present invention also provides a method for preparing the Co-As-Sn single crystal alloy as described above, wherein the method comprises mixing Co powder, As powder and Sn particles to obtain a mixture; then, heating and melting the mixture to obtain a prefabricated alloy melt; finally, cooling and crystallizing the prefabricated alloy melt, and separating excess Sn to obtain a Co-As-Sn single crystal alloy. Among them, by mixing Co powder, As powder and Sn particles, the uniform distribution of various elements in the Co-As-Sn single crystal alloy can be ensured, and the mixing process is simple and easy to control, which lays a good foundation for subsequent steps; heating and melting the mixture can ensure that the various elements in the mixture react fully to form a uniform prefabricated alloy melt, and optimize the microstructure and performance of the Co-As-Sn single crystal alloy; cooling and crystallizing the prefabricated alloy melt can arrange the elements in the prefabricated alloy melt in a specific order and manner to form a single crystal structure, and by separating excess Sn, it can ensure that the composition ratio of the Co-As-Sn single crystal alloy meets the design requirements. This method is simple to operate and has strong controllability. The prepared Co-As-Sn single crystal alloy is a linear magnetoresistance material with a wider operating temperature range, providing new material selection and technical support for the development of related fields.

[0017] The molar ratio of the Co powder, As powder and Sn particles is (0.95-1.05): (0.75-0.85): (9-11), wherein the excessive addition of Sn particles in the raw material can better ensure the effective doping of Sn, so that the elements in the finally prepared Co-As-Sn single crystal alloy are within the design range, ensuring that the Co-As-Sn single crystal alloy can meet the working requirements in a wider temperature range, and at the same time, helping to optimize the microstructure and properties of the alloy, so that it has better mechanical, magnetic and electrical properties.

[0018] The heating and melting temperature is 800°C to 850°C, and the holding time is 48 to 60 hours. Heating and melting within the temperature range of 800°C to 850°C can ensure that Co powder, As powder and Sn particles fully react and promote their uniform distribution in the melt, which helps to reduce component segregation and microstructural inhomogeneity in the alloy and improve the overall performance of the alloy. Holding for 48 to 60 hours can provide sufficient time for the growth of grains, so that the grains will gradually grow and tend to be uniform, thereby optimizing the microstructure of the alloy.

[0019] The heating time for heating and melting is 8 to 8.5 hours. Under this heating condition, the mixture can be heated evenly during the heating process, the thermal stress generated during the heating process can be reduced, the internal defects of the Co-As-Sn single crystal alloy can be reduced, and the quality of the Co-As-Sn single crystal alloy can be guaranteed.

[0020] The cooling rate of the cooling crystallization is 1-3°C / h, which can ensure that the alloy melt is uniformly crystallized during the cooling process, so that the elements in the alloy are arranged in a specific order and manner to form an orderly single crystal structure.

[0021] The prefabricated alloy melt is cooled to 500-550°C at a cooling rate of 1-3°C / h to separate the excess Sn, thereby obtaining a Co-As-Sn single crystal alloy melt. The separation of Sn in this temperature range is because the solubility of Sn is low at this temperature and it is easy to precipitate from the alloy melt. By separating the excess Sn, the Co-As-Sn single crystal alloy can be further purified to improve its single crystal quality.

[0022] The heating melting and cooling crystallization are both carried out under vacuum conditions. Heating melting under vacuum conditions can effectively reduce the contact between the alloy and gases such as oxygen and nitrogen in the air, thereby avoiding oxidation and pollution, helping to maintain the purity of the alloy and improving the performance of the final product. At the same time, the vacuum environment can reduce heat conduction and convection, so that the heat is more concentrated in the alloy melt, improving the heating efficiency; cooling crystallization under vacuum conditions can reduce the interference of the external environment on the crystallization process, so that the alloy can be arranged in a specific order and manner to form an ordered single crystal structure, which helps to improve the performance and stability of the single crystal alloy.

[0023] The present invention provides a Co-As-Sn single crystal alloy, which is prepared by the above method. After testing, the operating temperature range of the Co-As-Sn single crystal alloy is 2k~300k, which has a wider operating temperature range, can maintain high magnetic sensitivity and stability, and improve the anti-interference ability of the magnetic sensor, thereby meeting the accuracy requirements of the magnetic sensor under different temperature conditions.

[0024] Such as the application of Co-As-Sn single crystal alloy in magnetic sensors mentioned above. Co-As-Sn single crystal alloy has a wide operating temperature range and can maintain stable magnetic properties under extreme temperature conditions, so that the magnetic sensor can still maintain accurate measurement in high or low temperature environments, improving its stability and reliability. In addition, because Co-As-Sn single crystal alloy has a special magnetic and electronic structure, it can show higher magnetic sensitivity when used as a sensitive element of a magnetic sensor. High sensitivity means that the sensor can respond to changes in the magnetic field more accurately, thereby improving the accuracy of the measurement, so that magnetic sensors will play an important role in more fields. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 It is a schematic diagram of the preparation process of a Co-As-Sn single crystal alloy of the present invention.

[0026] Figure 2 This is a physical picture of the Co—As—Sn single crystal alloy prepared in Example 1 of the present invention.

[0027] Figure 3 This is the energy dispersive X-ray spectrometer spectrum of the Co-As-Sn single crystal alloy prepared in Example 1 of the present invention.

[0028] Figure 4 This is a curve diagram showing the relationship between magnetoresistance and magnetic field at different temperatures for the Co—As—Sn single crystal alloy prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0029] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.

[0030] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.

[0031] In this article, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values ​​within the range (including integers and fractions).

[0032] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”

[0033] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.

[0034] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0035] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples where specific conditions are not specified are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples are conventional commercial products unless otherwise specified, and their specifications are conventional specifications in the art. In the specification of the present invention and the following examples, unless otherwise specified, "%" means weight percentage, "part" means weight part, and ratio means weight ratio.

[0036] The present invention is further described in detail below in conjunction with specific embodiments, which are intended to explain the present invention rather than to limit it.

[0037] The invention discloses a Co-As-Sn single crystal alloy, comprising Co, As and Sn, wherein the molar ratio of Co, As and Sn is (0.95-1.05):(0.75-0.85):(0.33-0.43), preferably 1:0.8:0.38.

[0038] See also Figure 1 The present invention provides a method for preparing the Co-As-Sn single crystal alloy as described above, comprising: S1: Co powder, As powder and Sn particles are mixed to obtain a mixture, specifically: Co powder with a purity of 2N8 (99.8%), As powder with a purity of 5N (99.999%) and Sn particles with a purity of 5N (99.999%) are uniformly mixed in a protective atmosphere at a molar ratio of (0.95-1.05): (0.75-0.85): (9-11); preferably, the protective atmosphere is argon or helium, more preferably argon; the molar ratio of 2N8 (99.8%) Co powder, 5N (99.999%) As powder and 5N (99.999%) Sn particles is preferably 1:0.8:10; S2: heating and melting the mixture to obtain a prefabricated alloy melt, specifically: The mixture is heated to 800°C to 850°C under vacuum conditions for 8 to 8.5 hours, and kept at this temperature for 48 to 60 hours to obtain a prefabricated alloy melt; S3: Cooling down the prefabricated alloy melt to crystallize and separating the excess Sn to obtain a Co-As-Sn single crystal alloy, specifically: Under vacuum conditions, cooling the prefabricated alloy melt to 500°C to 550°C at a cooling rate of 1 to 3°C / h, separating excess Sn to obtain a Co-As-Sn single crystal alloy melt; preferably, separating excess Sn by centrifugation; The Co-As-Sn single crystal alloy melt is cooled to room temperature in air to obtain a Co-As-Sn single crystal alloy.

[0039] The present invention provides a Co-As-Sn single crystal alloy, which is prepared by the above method. After testing, the operating temperature range of the Co-As-Sn single crystal alloy is 2k~300k, which has a wider operating temperature range and can maintain high magnetic sensitivity and stability, improve the anti-interference ability of the magnetic sensor, thereby meeting the accuracy requirements of the magnetic sensor under different temperature conditions.

[0040] Such as the application of Co-As-Sn single crystal alloy in magnetic sensors mentioned above. Co-As-Sn single crystal alloy has a wide operating temperature range and can maintain stable magnetic properties under extreme temperature conditions, so that the magnetic sensor can still maintain accurate measurement in high or low temperature environments, improving its stability and reliability. In addition, because Co-As-Sn single crystal alloy has a special magnetic and electronic structure, it can show higher magnetic sensitivity when used as a sensitive element of a magnetic sensor. High sensitivity means that the sensor can respond to changes in the magnetic field more accurately, thereby improving the accuracy of the measurement, so that magnetic sensors will play an important role in more fields.

[0041] Example 1 In a glove box filled with argon, Co powder (purity 2N8 purchased from Alfa), As powder (purity 5N purchased from Aladdin) and Sn particles (purity 5N purchased from Sinopharm Reagent Network) were mixed and the mixture was placed in an alumina crucible; wherein the molar ratio of Co powder, As powder and Sn particles was 1:0.8:10; An alumina crucible is placed in a quartz tube and filled with quartz wool; the argon gas in the quartz tube is extracted by a mechanical pump-molecular pump group and then the quartz tube is packaged; the packaged quartz tube is placed in a box-type electric furnace for heating, and the temperature is raised from room temperature to 800°C over 8 hours, and the temperature is kept at 800°C for 48 hours to ensure that the raw materials are completely melted to obtain a prefabricated alloy melt; The prefabricated alloy melt was cooled and crystallized at a rate of 2°C / h, so that the sample precipitated crystals in the process. When the temperature dropped to 500°C, the quartz tube was inverted and placed in a centrifuge to separate the excess Sn, and then cooled to room temperature in air to obtain a Co-As-Sn single crystal alloy. The actual picture is as follows Figure 2 The figure shows an optical photograph of a typical Sn-doped CoAs single crystal, in which each grid length is 1 mm. From the figure, it can be seen that the sample has a regular rectangular morphology and can be directly tested without processing.

[0042] See also Figure 3 The Co-As-Sn single crystal alloy prepared in Example 1 was subjected to energy dispersive X-ray spectroscopy testing. It can be seen that the molar ratio of Co, As and Sn in the Co-As-Sn single crystal alloy is 1:0.8:0.38.

[0043] The Co-As-Sn single crystal alloy prepared in Example 1 was subjected to single crystal analysis, and the obtained single crystal analysis results are shown in the following table:

[0044] It can be seen from the analytical results that the Co-As-Sn single crystal alloy belongs to the hexagonal crystal system, its space group is P63 / mmc (No.194), and its lattice parameters are: a=3.5929 Å; b=3.5929 Å; c=5.2482 Å. It is a Sn-doped phase of CoAs single crystal (P63 / mmc; No.194), in which a part of the As position is replaced by Sn.

[0045] See also Figure 4 The magnetic properties of the Co-As-Sn single crystal alloy prepared in Example 1 were tested. It can be seen that the Co-As-Sn single crystal alloy, as a linear magnetoresistance material, has a linear increase in magnetoresistance with the increase in magnetic field intensity, and can still work normally at a low temperature of 2K, showing a wide temperature effect.

[0046] The Co-As-Sn single crystal alloy prepared in Example 1 was immersed in an aqueous solution with a hydrochloric acid concentration of 10% to 20% for more than 72 hours. After immersion, there were no cracks or pits on the surface of the Co-As-Sn single crystal alloy, indicating that the Co-As-Sn single crystal alloy can respond normally to changes in the external magnetic field under acidic conditions without being corroded.

[0047] Example 2 In a glove box filled with argon, Co powder (purity 2N8 purchased from Alfa), As powder (purity 5N purchased from Aladdin) and Sn particles (purity 5N purchased from Sinopharm Reagent Network) were mixed and the mixture was placed in an alumina crucible; wherein the molar ratio of Co powder, As powder and Sn particles was 0.95:0.75:9; An alumina crucible is placed in a quartz tube and filled with quartz wool; the argon gas in the quartz tube is extracted by a mechanical pump-molecular pump group and then the quartz tube is packaged; the packaged quartz tube is placed in a box-type electric furnace for heating, and the temperature is raised from room temperature to 800°C over 8 hours, and the temperature is kept at 800°C for 50 hours to ensure that the raw materials are completely melted to obtain a prefabricated alloy melt; The prefabricated alloy melt was cooled and crystallized at a rate of 1°C / h, so that the sample precipitated crystals in the process. When the temperature was cooled to 520°C, the quartz tube was inverted and placed in a centrifuge to separate excess Sn, and then cooled to room temperature in air to obtain a Co-As-Sn single crystal alloy.

[0048] Example 3 In a glove box filled with argon, Co powder (purity 2N8 purchased from Alfa), As powder (purity 5N purchased from Aladdin) and Sn particles (purity 5N purchased from Sinopharm Reagent Network) were mixed, and the mixed mixture was placed in an alumina crucible; wherein the molar ratio of Co powder, As powder and Sn particles was 1.05:0.85:9.5; Put an alumina crucible into a quartz tube and insert quartz wool; use a mechanical pump-molecular pump group to extract argon gas in the quartz tube and then package the quartz tube; place the packaged quartz tube in a box-type electric furnace for heating, raise the temperature from room temperature to 830°C over 8 hours, and keep it at 830°C for 60 hours to ensure that the raw materials are completely melted to obtain a prefabricated alloy melt; The prefabricated alloy melt was cooled and crystallized at a rate of 3°C / h, so that the sample precipitated crystals in the process. When the temperature was cooled to 550°C, the quartz tube was inverted and placed in a centrifuge to separate excess Sn, and then cooled to room temperature in air to obtain a Co-As-Sn single crystal alloy.

[0049] Example 4 In a glove box filled with argon, Co powder (purity 2N8 purchased from Alfa), As powder (purity 5N purchased from Aladdin) and Sn particles (purity 5N purchased from Sinopharm Reagent Network) were mixed and the mixture was placed in an alumina crucible; wherein the molar ratio of Co powder, As powder and Sn particles was 1:0.8:10; Put an alumina crucible into a quartz tube and insert quartz wool; use a mechanical pump-molecular pump group to extract the argon gas in the quartz tube and then package the quartz tube; place the packaged quartz tube in a box-type electric furnace for heating, raise the temperature from room temperature to 850°C over 8.5 hours, and keep it at 850°C for 60 hours to ensure that the raw materials are completely melted to obtain a prefabricated alloy melt; The prefabricated alloy melt was cooled and crystallized at a rate of 2°C / h, so that the sample precipitated crystals in the process. When the temperature was cooled to 500°C, the quartz tube was inverted and placed in a centrifuge to separate excess Sn, and then cooled to room temperature in air to obtain a Co-As-Sn single crystal alloy.

[0050] In summary, the present invention provides a Co-As-Sn single crystal alloy, a preparation method and an application thereof. The present invention prepares a Co-As-Sn single crystal alloy by doping Co and As with Sn elements. The doping with Sn elements can change the band structure and Bailey curvature of the alloy, thereby affecting its magnetoresistance behavior, so that the prepared Co-As-Sn single crystal alloy can still work normally at low temperatures as a linear magnetoresistance material, and has a wider working temperature range, thereby better meeting the use requirements of magnetic sensors, so that magnetic sensors will play an important role in more fields.

[0051] The above description is only a preferred embodiment of the present invention and is not intended to impose any limitation on the technical solution of the present invention. Those skilled in the art should understand that, without departing from the spirit and principles of the present invention, the technical solution can also be subjected to several simple modifications and substitutions, and these modifications and substitutions are also within the scope of protection covered by the claims.

Claims

1. A Co-As-Sn single crystal alloy, characterized in that: The invention comprises Co, As and Sn, wherein the molar ratio of Co, As and Sn is (0.95-1.05): (0.75-0.85): (0.33-0.43).

2. The method for preparing a Co-As-Sn single crystal alloy according to claim 1, characterized in that: include: Mixing Co powder, As powder and Sn particles to obtain a mixture; The mixture is heated and melted to obtain a prefabricated alloy melt; The prefabricated alloy melt is cooled and crystallized, and excess Sn is separated to obtain a Co-As-Sn single crystal alloy.

3. The method for preparing a Co-As-Sn single crystal alloy according to claim 2, characterized in that: The molar ratio of the Co powder, As powder and Sn particles is (0.95-1.05): (0.75-0.85): (9-11).

4. The method for preparing a Co-As-Sn single crystal alloy according to claim 1, characterized in that: The heating and melting temperature is 800° C. to 850° C., and the heat preservation time is 48 to 60 hours.

5. The method for preparing a Co-As-Sn single crystal alloy according to claim 3, characterized in that: The heating time for the heating and melting is 8 to 8.5 hours.

6. The method for preparing a Co-As-Sn single crystal alloy according to claim 1, characterized in that: The cooling rate of the cooling crystallization is 1-3°C / h.

7. The method for preparing a Co-As-Sn single crystal alloy according to claim 1, characterized in that: The method of cooling the prefabricated alloy melt to crystallize and separate the excess Sn to obtain the Co-As-Sn single crystal alloy is as follows: The prefabricated alloy melt is cooled to 500°C to 550°C at a cooling rate of 1 to 3°C / h, and excess Sn is separated to obtain a Co-As-Sn single crystal alloy melt; The Co-As-Sn single crystal alloy melt is cooled to room temperature in air to obtain a Co-As-Sn single crystal alloy.

8. The method for preparing a Co-As-Sn single crystal alloy according to claim 1, characterized in that: The heating melting and cooling crystallization are both carried out under vacuum conditions.

9. A Co-As-Sn single crystal alloy, characterized in that: Prepared by the method described in any one of claims 2 to 8, the Co—As—Sn single crystal alloy has an operating temperature range of 2K to 300K.

10. Use of the Co-As-Sn single crystal alloy according to claim 1 or 9 in a magnetic sensor.

Citation Information

Patent Citations

  • Mn50CoxNiySnz high-temperature ferromagnetic shape memory alloy material and preparation methods thereof

    CN102115914A

  • Mn-Ni-Sn-Co alloy ribbon and preparation method thereof

    CN106119661A

  • Magnetic refrigeration material and preparation method thereof

    CN107841674A

  • BULK TYPE MANGANESE SILICIDE SINGLE CRYSTAL OR POLYCRYSTAL DOPED WITH Ga OR Sn, AND METHOD OF MANUFACTURING THE SAME

    JP2011210845A

  • Mgb2 based powder for the production of super conductOrs, method for the use and production thereof

    US20040204321A1